Impact of Nematode Infections on Non-specific and Vaccine-Induced Humoral Immunity in Dual-Purpose or Layer-Type Chicken Genotypes - Daş, Gürbüz; Auerbach, Monika; Stehr, Manuel; Sürie, Christian; Metges, Cornelia C.; Gauly, Matthias; Rautenschlein, Silke (Frontiers in Veterinary Science, 2021)
Nematode infections may induce immune-modulatory effects and influence host-immune responses to other pathogens. The aim of the study was to investigate whether a mixed nematode-infection influences non-specific and vaccine-induced humoral immunity against Newcastle Disease Virus (NDV), Infectious Bronchitis Virus (IBV) and Avian Metapneumovirus (AMPV) in already vaccinated hens of a dual-purpose (Lohmann Dual, LD) or a layer genotype (Lohmann Brown Plus; LB). Until 17 weeks-of-age, LD (n=70) and LB (n=109) hens were vaccinated against major bacterial and viral diseases and coccidiosis. At 24 weeks-of-age, the hens received either a placebo or an oral inoculation of 1,000 infectious eggs of A. galli and H. gallinarum. Plasma total immunoglobulin (Ig) isotypes (IgY, IgM, IgA) levels and vaccine-induced antibody titers against NDV, IBV and AMPV were determined from 2 to 18 weeks post infection (wpi). Infections had no suppressing effect on total Ig isotypes IgY, IgM, and IgA as well as on vaccine-induced antibody titers against NDV, IBV and AMPV (P>0.05). Overall, LB hens had higher levels of IgY, IgM and IgA than those of LD hens (P≤0.05). There were no differences between IBV titers of the two genotypes (P>0.05). Independent of infection status of the hens, NDV titers were higher in LB hens than in LD hens at wpi 2 (P<0.05), but not in following weeks (P>0.05). Uninfected LD hens had lower AMPV titers than their infected counterparts at 6 and 14 wpi (P<0.05). Regardless of nematode infection, LD hens revealed a higher risk of responding weak to vaccination against NDV (odds ratio = 5.45; P=0.021) and AMPV (odds ratio = 13.99, P<0.001) than did LB hens (P>0.05). We conclude that nematode infections have no adverse effects on non-specific and vaccine-induced humoral immunity in either genotype. LB hens have higher levels of total immunoglobulin isotypes than LD hens. Except for IBV, vaccine-induced humoral immune responses show a dependency on genotype. Dual-purpose hens show lower responsiveness to vaccinations against NDV and AMPV, possibly due to factors associated with increased body fat reserves in this genotype.